2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7320085
|View full text |Cite
|
Sign up to set email alerts
|

Real time heart rate variability assessment from Android smartphone camera photoplethysmography: Postural and device influences

Abstract: The aim of this paper is to present a smartphone based system for real-time pulse-to-pulse (PP) interval time series acquisition by frame-to-frame camera image processing. The developed smartphone application acquires image frames from built-in rear-camera at the maximum available rate (30 Hz) and the smartphone GPU has been used by Renderscript API for high performance frame-by-frame image acquisition and computing in order to obtain PPG signal and PP interval time series. The relative error of mean heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…Since then, other studies have aimed to extract PRV information from video and image PPG, and to understand how frame rate could affect PRV (Sun et al 2012); which colour channels (e.g. RGB, CIE, CGO) could give more reliable PRV results (Mcduff et al 2014); how the camera used for obtaining the images could alter PRV results (Guede-Fernández et al 2015); how far could the camera be positioned from the skin (Blackford et al 2016); and the effects of different techniques for obtaining PPG information from the images on PRV information (Alghoul et al 2017, Rodríguez andRamos-Castro 2018).…”
Section: Technical Considerations For Pulse Rate Variability Analysismentioning
confidence: 99%
“…Since then, other studies have aimed to extract PRV information from video and image PPG, and to understand how frame rate could affect PRV (Sun et al 2012); which colour channels (e.g. RGB, CIE, CGO) could give more reliable PRV results (Mcduff et al 2014); how the camera used for obtaining the images could alter PRV results (Guede-Fernández et al 2015); how far could the camera be positioned from the skin (Blackford et al 2016); and the effects of different techniques for obtaining PPG information from the images on PRV information (Alghoul et al 2017, Rodríguez andRamos-Castro 2018).…”
Section: Technical Considerations For Pulse Rate Variability Analysismentioning
confidence: 99%
“…The SPPG signal has been obtained using a smartphone application developed previously by our research group that is fully described in [26]. Briefly, the smartphone application acquires PPG from the smartphone's built-in rear camera at 30 Hz.…”
Section: Smartphone-based Photoplethysmography Applicationmentioning
confidence: 99%
“…Although methods have been proposed to reduce the impact of noise and artifacts in HRV measurement, other studies have investigated the effect of mobile phone models on the SD of beat-to-beat error measurement (SDE) of HRV indices. In 1 study, 2 different mobile phone models (Samsung S5 and Motorola) showed significant device influence in the supine posture measurement, with the Motorola model having a higher SDE than the Samsung S5 [76].…”
Section: Resultsmentioning
confidence: 99%